IMPLEMENTASI PRINSIP-PRINSIP PENDIDIKAN ORDO SAUDARA DINA KONVENTUAL PADA PEMBINAAN DI BIARA SANTO BONAVENTURA-PEMATANGSIANTAR - Purba, Asrot; Sinaga, Raidin; Gustardi, Aurelius (LOGOS, 2025)
The essence of formation is the call to follow Christ and His gospel. Formation for priesthood and member of Consecrated Life must be orientated towards identification with Christ. This identification is confirmed by faith as one's personal encounter with Christ and is lived out as a call to a life of constant repentance. Formation really means a willingness to learn by doing what God says. The ultimate formator is God Himself. God is the only unique first in the life of a religious. Formation in the Saint Bonaventure Abbey takes the form of a universal pattern of religious life with the prevailing dimensions of formation (human, spiritual, intellectual, and pastoral). These dimensions of formation also be elaborated with the application of the order's charism. The application of the order's charism is contained in the educational principles applied in formation, namely: Education is the work of the Trinity, the likeness of Christ, and the cultivation of basic Franciscan values. These dimensions of formation and these educational principles form the formandi’s identity.